2016
DOI: 10.1038/srep24749
|View full text |Cite
|
Sign up to set email alerts
|

Response of AM fungi spore population to elevated temperature and nitrogen addition and their influence on the plant community composition and productivity

Abstract: To examine the influence of elevated temperature and nitrogen (N) addition on species composition and development of arbuscular mycorrhizal fungi (AMF) and the effect of AMF on plant community structure and aboveground productivity, we conducted a 5-year field experiment in a temperate meadow in northeast China and a subsequent greenhouse experiment. In the field experiment, N addition reduced spore population diversity and richness of AMF and suppressed the spore density and the hyphal length density (HLD). E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 57 publications
5
40
0
Order By: Relevance
“…Moreover, Wilson et al (2016) concluded that the direct effect of increasing 3°C the temperature decreases AMF colonization, and this appeared to be regionally consistent across the Mediterranean climate gradient. On the other hand, although the growth of external hyphae and the diversity of AMF species can increase at high temperatures ( Hawkes et al, 2008 ; Zhang et al, 2016 ), the mycorrhizal activity generally decreases ( Mohan et al, 2014 ). Furthermore, in a warmer world, the presumed enhanced growth of AMF hyphae is unlikely to balance the carbon losses to the atmosphere from the AMF respiration ( Hawkes et al, 2008 ).…”
Section: Effects Of Changing Environments On the Arbuscular Mycorrhizmentioning
confidence: 99%
“…Moreover, Wilson et al (2016) concluded that the direct effect of increasing 3°C the temperature decreases AMF colonization, and this appeared to be regionally consistent across the Mediterranean climate gradient. On the other hand, although the growth of external hyphae and the diversity of AMF species can increase at high temperatures ( Hawkes et al, 2008 ; Zhang et al, 2016 ), the mycorrhizal activity generally decreases ( Mohan et al, 2014 ). Furthermore, in a warmer world, the presumed enhanced growth of AMF hyphae is unlikely to balance the carbon losses to the atmosphere from the AMF respiration ( Hawkes et al, 2008 ).…”
Section: Effects Of Changing Environments On the Arbuscular Mycorrhizmentioning
confidence: 99%
“…In the ARB: VES relation was observed maximum value in the treatments UFLA351, UFLA372, and UFLA401 with 300, 100, and 0 mg Kg -1 N, respectively, which characterizes a beneficial interaction between these UFLAs isolates and rice plants. However, the increase in nitrogen level did not influenced this variable, whose data were not adjusted for any regression model in all treatments (Table 1) According to Zhang et al (2016), the addition of nitrogen fertilizer reduced in 14% the AMF population in rice cultivation. At current work, in the control treatment (without AMF inoculum) with 600 mg Kg -1 N the number of mycorrhizal spores was reduced to 41.4% in relation to the control without nitrogen.…”
Section: Colonization Of Rice Plants By Endophytic Microorganisms Witmentioning
confidence: 99%
“…Püschel et al (2016) mentioned that nitrogen fertilizers stimulated mycorrhizal colonization of grass plants and promoted plant growth with immobilization of nitrogen to the biomass of mycorrhizal plants. Zhang et al (2016) found that AMF colonization associated with nitrogen fertilization reduces the negative effect of high temperature on poaceaus biomass production. Teutscherova et al (2019) verified that nitrogen absorption by mycorrhizal plants reduces the losses of this element to the atmosphere, mainly in nitrous oxide form, one of the gases of the greenhouse effect and stimulates the development by bacteria that oxide the ammonia, which decompose organic matter.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the development and species composition of AMF are often influenced by global change, such as warming and N input [33,34]. In our previous research [35], we found that AMF altered the species composition and productivity under warming and nitrogen (N) addition. However, the mechanism by which AMF affect plant community composition and productivity under warming and N addition is not well understood.…”
Section: Introductionmentioning
confidence: 99%